2008
DOI: 10.1016/j.ejphar.2007.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Doxazosin induces apoptosis of cells expressing hERG K+ channels

Abstract: The antihypertensive drug doxazosin has been associated with an increased risk for congestive heart failure and cardiomyocyte apoptosis. Human ether-a-go-go-related gene (hERG) K(+) channels, previously shown to be blocked by doxazosin at therapeutically relevant concentrations, represent plasma membrane receptors for the antihypertensive drug. To elucidate the molecular basis for doxazosin-associated pro-apoptotic effects, cell death was studied in human embryonic kidney cells using three independent apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…HERG is overexpressed in a wide range of human cancers, such as gastric cancer, colorectal cancer, endometrial cancer and glioblastoma multiforme (11)(12)(13)(14). Three main functions relevant to tumor cell biology can be ascribed to HERG activity: tumor cell proliferation (15), tumor cell invasiveness (12) and tumor neoangiogenesis (16). Because of their oncogenic properties, distribution, modulation and pharmacology, HERG has gained great interest as potential diagnostic markers and membrane therapeutic targets for cancer (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…HERG is overexpressed in a wide range of human cancers, such as gastric cancer, colorectal cancer, endometrial cancer and glioblastoma multiforme (11)(12)(13)(14). Three main functions relevant to tumor cell biology can be ascribed to HERG activity: tumor cell proliferation (15), tumor cell invasiveness (12) and tumor neoangiogenesis (16). Because of their oncogenic properties, distribution, modulation and pharmacology, HERG has gained great interest as potential diagnostic markers and membrane therapeutic targets for cancer (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…14,16) It has been reported that calcium channel blocking can compensate for the proarrhythmic effects of the HERG blockade. 27,28) Nonetheless, our findings provide a direct cellular mechanism for IM-induced QT interval prolongation and cardiac arrhythmia. Direct inhibition of the HERG channel may be of greater concern when IM is used in patients with congenital long QT syndrome, in patients with electrolyte abnormalities such as hypokalemia, or in patients receiving other QT intervalprolonging drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-apoptotic effects have been observed with low-affinity hERG current inhibitors (Thomas et al, 2008;Gong et al, 2010;Obers et al, 2010;Staudacher et al, 2011a). In contrast, zolpidem did not affect apoptosis of HL-1 cardiac myocytes.…”
Section: Lack Of Pro-apoptotic Effects Despite Inhibition Of Herg Potmentioning
confidence: 93%
“…Pharmacological inhibition of hERG channels has been shown to promote apoptosis (Thomas et al, 2008;Obers et al, 2010;Jehle et al, 2011;Staudacher et al, 2011a). To assess whether zolpidem exerts similar actions, apoptotic cell death was studied in HL-1 cells using TUNEL staining (Figure 7).…”
Section: Zolpidem Is Not Associated With Apoptotic Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation